Greek sacred law : a collection of new documents (NGSL) - Lupu, Eran. (Religions in the Graeco-Roman World, 2005)
This work contains two parts. Part I constitutes a guide to the corpus of Greek sacred law and its contents. A discussion of the history of the corpus and the principles governing its composition is followed by a detailed review of its contents, in which the evidence is classified according to subject matter. Part II contains inscriptions published since the late 1960s from all around the Greek world excluding Cos and Asia Minor (checklists for these are appended). The text of each inscription is presented alongside restorations, epigraphical commentary, translation, and a comprehensive running commentary. Most of the inscriptions are illustrated. The volume should prove useful to scholars of Greek religion, historians, and epigraphists.